Rheological properties measurement of Mucuna solannie as cement slurry extender: characterization and verification using rheological models - K. Chinwuba, Igwilo; Nnaemeka, Uwaezuoke; Nwanwe, Onyebuchi; C. Vivian, Amaefule; U. Raji, Abubakar (International Journal of Engineering and Technology, 2020)
Rheological properties of lead cement slurry with Mucuna solannie admixture as an extender was measured in accordance with API standard. Bentonite extender was used as a control. The elemental and oxide compositions of Mucuna solannie were determined using Scanning Electron Microscope and X-Ray Florescence (XRF) methods, and rheological properties were obtained using rheometer after conditioning. The rheological data from Mucuna solannie and bentonite lead slurries were validated using Bingham Plastic and Herschel-Bulkley models. The result showed that Mucuna solannie contains high carbon atomic concentration and is responsible for its high rheological properties values. Lead slurry prepared with Mucuna solannie gave higher plastic viscosity, yield point and gel strength than that of bentonite. Herschel-Bulkley model described the rheological properties better than Bingham Plastic model. Due to high rheological properties values of the slurry prepared with Mucuna solannie, dispersant is needed for the optimization of the yield point and gel strength. Â